EFFICIENCY OF APPLICATION OF INNOVATIVE BIOMECHANICAL ORTHOPEDIC INSTRUMENTS IN THE PATHOLOGY OF THE BONEJOINT SYSTEM - Madaminov S.M; Madaminov A.S. (Scholar Express Journals, 2023)
This article shows the results of treatment of diseases of the musculoskeletal system caused by violations of the rules of biomechanics, along with the use of medicines, using an innovative biomechanical orthopedic device that helps restore the biomechanical properties of the body.
Keywords: principles of biomechanics; joint structure; compressing and suppressing surfaces